Exercise Performed Concomitantly with Particulate Matter Exposure Inhibits Lung Injury - Silva-Renno, Adriano; Baldivia, Guilherme Crisitanini; Oliveira-Junior, Manoel C.; Brandao-Rangel, Maysa Alves Rodrigues; El-Mafarjeh, Elias; Dolhnikoff, Marisa; Mauad, Thaís; Britto, Jôse Mára; Saldiva, Paulo Hilário Nascimento; Oliveira, Luis Vicente Franco; Ligeiro-Oliveira, Ana P.; Graudenz, Gustavo Silveira; Vieira, Rodolfo Paula (International Journal of Sports Medicine, 2018)
Air pollution is a growing problem worldwide, inducing and exacerbating several diseases. Among the several components of air pollutants, particulate matter (PM), especially thick (10–2.5 µm; PM 10) and thin (≤2.5 µm; PM 2.5), are breathable particles that easily can be deposited within the lungs, resulting in pulmonary and systemic inflammation. Although physical activity is strongly recommended, its effects when practiced in polluted environments are questionable. Therefore, the present study evaluated the pulmonary and systemic response of concomitant treadmill training with PM 2.5 and PM 10 exposure. Treadmill training inhibited PM 2.5- and PM 10-induced accumulation of total leukocytes (p<0.001), neutrophils (p<0.001), macrophages (p<0.001) and lymphocytes (p<0.001) in bronchoalveolar lavage (BAL), as well as the BAL levels of IL-1beta (p<0.001), CXCL1/KC (p<0.001) and TNF-alpha (p<0.001), whereas it increased IL-10 levels (p<0.05). Similar effects were observed on accumulation of polymorphonuclear (p<0.01) and mononuclear (p<0.01) cells in the lung parenchyma and in the peribronchial space. Treadmill training also inhibited PM 2.5- and PM 10-induced systemic inflammation, as observed in the number of total leukocytes (p<0.001) and in the plasma levels of IL-1beta (p<0.001), CXCL1/KC (p<0.001) and TNF-alpha (p<0.001), whereas it increased IL-10 levels (p<0.001). Treadmill training inhibits lung and systemic inflammation induced by particulate matter.
Keywords: exercise immunology; lung immunology; air pollution; particulate matter; lung inflammation